The benefits of automated dispensing machine for hospital pharmacy in Indonesia: situation, implementation, and feasibility - Haryman Utama Suryadinata (GHMJ (Global Health Management Journal), 2017)
Background: Pharmacy as the main core of hospital is responsible for the quality and safety of medicines.Yet the numbers of medication errors are still high. Automated Dispensing Machine (ADM) is one of the solutions to reduce the dispensing errors in pharmacy. Many countries had studied and proved that the use of ADM gives more benefit than liability. However, ADM is considered as something new, a “nice to have” product.Aims: This study will explain the benefits of ADM especially in Indonesian hospital pharmacy.Methods: Systemic Review with PRISMA method uses 5 databases as Scopus, Springerlink, Google Scholar, Science Direct and ProQuest, with keywords Automated Dispensing Machine, Automated Dispensing Device, Automated Dispensing System, Automated Drug Dispensing System, or Robotic Dispensing System. The inclusion criteria are all the studies that showed any impact in minimum of one aspect ofADM in hospital.Results: There are 13 studies that explained ADM benefits such as increase staff satisfaction for the nurse and pharmacist, reduce dispensing errors about 35% or up to reducing all dispensing errors, time saving until 50% in peak hours and cost analysis and effectiveness. The cost anaylsis such as inventory stock reduction, increases the cost saving.Conclusion:In Indonesia, it needs many considerations to implement ADM but it had already installed in 1 Indonesia Hospital. This hospital had proved that ADM can reduce dispensing errors and can solve some pharmacy problem such as the human resources problems and the long waiting time.With the proven benefits of ADM, it is justified for Indonesian hospital to implement ADM and information system in their pharmacy. The effectiveness will perceive the pharmacy andpositively affect to all related departments in hospital. Keywords: Automated dispensing machine, automated dispensing system, automated dispensing device, robotic dispensing system, automated drug dispensing system